Evaluation of antinociceptive and anti-inflammatory effects of venlafaxine in the rat - (:unkn) unknown (My University, 2005)
The aim of this study was to test antinociceptive properties of venlafaxine in rats with carrageenan-induced pain and inflammation. Pain was provoked with carrageenan (1%) injection into the plantar surface of the rat paw-pad. The effect of venlafaxine on carrageenan-induced mechanical hypersensitivity, mechanical stimulation response (the von Frey monofilament test) as well as the size of carrageenan-induced paw edema were tested at 2 to 24 hours following the toxin injection into the rat paw-pad. Pretreatment with venlafaxine significantly reduced or completely abolished the enhanced sensitivity to mechanical stimuli provoked by peripheral carrageenan injection. The study demonstrated the efficacy of peripherally applied venlafaxine pretreatment on the pain component of inflammatory process.
Keywords: Anti-inflammatory; Antinociceptive; Rat; Venlafaxine